Tasación de predios agropecuarios; como recurso productivo, en la ciudad de Tamshiyacu, distrito de Fernando Lores. Región Loreto. 2020 - Salazar Ramirez, Jose Angel (2024)
The study consisted of tapping the agricultural properties in the locality of Tamshiyacu as a productive resource since rural areas constitute the means of production of products or crops, whose value depends on their production capacity, quantity and quality and that, at the time of starting the study, we did not have information on the economic valuation of rural properties and/or properties in the locality. The objective of the study was to economically determine these properties according to the Valuation Standards that govern Peru with respect to the application of rural land tariffs, Title IV, Article 4.1. The type of research was basic non-experimental; the Research Level was Descriptive and Cross-sectional. The appraisal of the plots was carried out with the help of agricultural producers located on the Yavarí-Miri road, in a population of 80 farmers), carrying out convenience sampling with 21 families, using the survey technique and the questionnaire as the main instrument. The data obtained were tabulated, which led to the elaboration of tables and graphs. The results led to the conclusion that the prices of the properties were 11,803.62, 17,030.7, 26,097.37 and 29,600.81 soles as the base price per hectare, according to their technical and physical characteristics obtained in each natural space, generating an optimization of the formalization processes of the rural properties and also, the institutions involved such as the DRAL, Under the authority of the Regional Management of Economic Development, through the Directorate of Legal Physical Sanitation of Agrarian Property – DISAFILPA, SUNARP and COFOPRI guarantee the titling and sale of rural land.